Given "(D^3-3D\u00b2D'+ D'\u00b3) z= 0" where "D = \\frac{\\partial}{\\partial x}, D' = \\frac{\\partial}{\\partial y}" .
Since, "D^3-3D\u00b2D'+ D'\u00b3" is irreducible in linear factors,
assume solution is "z = \\sum A e^{hx+ky}" .
Now. "(D^3-3D\u00b2D'+ D'\u00b3)z =(h^3-3h^2k+k^3) \\sum{Ae^{hx+ky}} = 0" "\\implies h^3 - 3h^2 k +k^3 = 0" .
Hence, "z = \\sum A e^{hx+ky}" is solution of given differential equation where h and k holds the condition "h^3 - 3h^2 k +k^3 =0" .
Comments
Leave a comment